Furcation management: a viable surgical for apical migration of the gingival margin on mandibular molar - Abdul Aziz, Abdul Azim Asy; Ahmad, Aimi Amalina; Sabarudin, Muhammad Annurdin; Mohd Hanifah, Muhammad Hadi; Roslan, Uzair (IIUM Journal of Orofacial and Health Sciences, 2026)
Furcation involvement (FI) poses significant challenges in periodontal management due to anatomical complexities and limited accessibility for cleaning, often resulting in the progression of periodontal diseases if not properly addressed and treated. This case report presented a 50-year-old male patient with gingival recession and FI in the left mandibular molar, tooth 36. A f) procedure was performed under local anaesthesia, involving incision and flap reflection, exposure and debridement of the furcation area, and apical repositioning of the flap to facilitate plaque control and reduce disease progression risk. Post-operative healing was satisfactory, with no signs of inflammation observed at the two-week follow-up. Supportive p therapy (SPT) was implemented to maintain long-term satisfactory clinical outcomes. This case highlights the efficacy of FP as a treatment modality for FI, emphasising the significance of meticulous and proper case selection.